Criminal Liability for Circumcision Malpractice: Ibn Qayyim’s Jurisprudence and Indonesian Criminal Law - Maulidar, Rona; Syah, Yuhasnibar; binti Awang, Nurulbahiah (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This article analyzes criminal liability for malpractice committed by circumcision (khitan) practitioners, as outlined by Ibn Qayyim al-Jawziyyah, and examines its relevance to positive law in Indonesia. The study is motivated by fundamental differences in the determination of criminal liability between classical Islamic legal perspectives and national law. This research is normative legal research employing a statute approach and a conceptual approach. Data were collected through library research, including primary, secondary, and tertiary legal materials such as statutory regulations, the works of Ibn Qayyim al-Jawziyyah, and relevant scholarly literature. The data were analyzed using a descriptive-analytical method that integrated perspectives on positive law and Islamic normative law. The findings indicate that, according to Ibn Qayyim, a circumcision practitioner must possess both professional competence and a valid practice license. A competent and licensed practitioner is not subject to criminal liability for patient harm in the absence of intentional wrongdoing, whereas an unqualified and unlicensed practitioner may be held criminally liable. In contrast, under Indonesian positive law, criminal liability is not solely based on intent (mens rea) but also encompasses negligence and recklessness that result in harm; thus, a practitioner may still be held criminally liable despite having competence and a valid license. Accordingly, Ibn Qayyim’s view appears less relevant within the framework of Indonesian positive law regarding criminal liability. Nevertheless, his emphasis on strict requirements for competence and licensing has preventive value, helping minimize malpractice and enhance professional standards in medical practice.